2011
DOI: 10.1093/gerona/glr025
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Myostatin and Myostatin-Interacting Proteins Do Not Differ Between Young and Sarcopenic Elderly Men

Abstract: Sarcopenia is the loss of muscle size and function during ageing. The aim of this study was to test whether serum concentrations of myostatin and interacting proteins (GASP-1, FLRG, and follistatin) differed between young and elderly sarcopenic men. Isometric knee extensor maximal voluntary contraction and quadriceps cross-sectional area (magnetic resonance imaging measurement) were significantly higher in young (22 ± 2 years; 266 ± 54 N/m; 8,686 ± 1,154 mm(2)) than in mildly sarcopenic (69 ± 3 years; 183 ± 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
72
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 43 publications
15
72
4
Order By: Relevance
“…Although Myostatin is doubtless an inhibitor of skeletal muscle mass development, its role in muscle atrophy remains unclear. Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations,41, 42, 43 recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass 44, 45, 46. In agreement with our results, Breitbart et al .…”
Section: Discussionsupporting
confidence: 89%
“…Although Myostatin is doubtless an inhibitor of skeletal muscle mass development, its role in muscle atrophy remains unclear. Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations,41, 42, 43 recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass 44, 45, 46. In agreement with our results, Breitbart et al .…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, total myostatin serum levels were higher than those found using immunoassays specific for the active C-terminal dimer (18,35). In our study, total myostatin levels correlated negatively with fat mass, mainly central fat mass, but not with lean mass or grip strength (16).…”
Section: Discussioncontrasting
confidence: 63%
“…Yet, data for the relationship between circulating myostatin and agerelated muscle loss have been scarce and conflicting. While an earlier study reported significant elevations in serum myostatin levels with advancing age and declining lean mass (Yarasheski et al 2002), more recent studies had failed to support these findings (Hofmann et al 2015;Ratkevicius et al 2011). Intriguingly, we have observed myostatin to confer deleterious effects for sarcopenia only in older male adults that, if corroborated, has important clinical significance in selection of individuals most likely to benefit from myostatin blocking therapy.…”
Section: Discussionmentioning
confidence: 43%